2020
DOI: 10.1177/0960327120960768
|View full text |Cite
|
Sign up to set email alerts
|

Morroniside suppresses hydrogen peroxide-stimulated autophagy and apoptosis in rat ovarian granulosa cells through the PI3K/AKT/mTOR pathway

Abstract: Previous evidences have indicated that granulosa cells play a critical role in follicular growth. Hydrogen peroxide (H2O2)-induced oxidative stress has been associated with ovarian granulosa cell apoptosis and ovarian function. Recently, a study highlighted the protective role of morroniside against H2O2-induced damage. In this study, we aimed to investigate the effects of morroniside on H2O2-stimulated rat ovarian granulosa cells and its underlying molecular mechanisms. Our results showed that H2O2 treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 38 publications
4
16
0
Order By: Relevance
“…Prieto L et al con rmed that the levels of ROS in the follicular uid of infertility patients with endometriosis are increased, while the levels of T-AOC and SOD are generally decreased [29]. Morroniside could suppressed autophagy and apoptosis in rat ovarian GCs through the PI3K/AKT/mTOR pathway [22]. Our study showed that morroniside could inhibited the levels of ROS and 8-OHdG and MDA content and increased the expression of SOD and NQO1in human ovarian GCs (Figs.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Prieto L et al con rmed that the levels of ROS in the follicular uid of infertility patients with endometriosis are increased, while the levels of T-AOC and SOD are generally decreased [29]. Morroniside could suppressed autophagy and apoptosis in rat ovarian GCs through the PI3K/AKT/mTOR pathway [22]. Our study showed that morroniside could inhibited the levels of ROS and 8-OHdG and MDA content and increased the expression of SOD and NQO1in human ovarian GCs (Figs.…”
Section: Discussionsupporting
confidence: 52%
“…It has a variety of biological activities, such as antioxidant, anti-apoptotic, anti-in ammatory [17][18][19], which can relieve nerve pain, improve cardiovascular and liver functions [20,21]. Deng et al have con rmed that morroniside inhibitd autophagy in rats ovarian GCs by regulating the PI3K/AKT/mTOR pathway [22]. However, the effect of morroniside on oxidative stress of GCs induced by H 2 O 2 is largely unclear.…”
Section: Introductionmentioning
confidence: 99%
“…MR has been documented to possess anti-oxidation, antiinflammation, and anti-apoptosis properties (Gao et al, 2020;Deng et al, 2021;Park et al, 2021). It can exert a neuroprotective role in neurodegenerative diseases by eliminating ROS to enhance the total antioxidant capacity of the rat cortex, thereby preventing nerve cells from H 2 O 2 -induced oxidation injury (Wang et al, 2009;Yao et al, 2009;Zhang et al, 2017c;Li B et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…OS injury initiates autophagy by inhibiting the PI3K/AKT signaling pathway, promoting the dissociation between mTORC1 and ULK1, further phosphorylating autophagy-related proteins such as Atg13 [ 184 ]. It was found that H 2 O 2 intervention in granulosa cells inhibited the PI3K/AKT/mTOR pathway and increased LC3-II/LC3-I and Beclin-1 expression [ 185 ]. Activation of AKT regulates the cell cycle by regulating the function of cell cycle proteins (cyclins).…”
Section: Os-related Signaling Pathways In Ovarian Agingmentioning
confidence: 99%